Participatory rural innovation lab: Towards a sustainable agri-food system in the context of climate change - Clavijo, Neidy; Rodriguez, Luz Angela; Vanegas Cubillos, Martha (2025)
As climate change impacts become more apparent, agri-food systems face increasing pressure to innovate for adaptation and mitigation. Innovation processes that address both, must consider local ecological, cultural, and social contexts to ensure sustainability. Living labs present an opportunity for communities to take on the roles of co-designers and managers of sustainable agroecosystems.